Kualitas Pelayanan dan Persepsi Harga terhadap Niat Pelanggan untuk Menggunakan Kembali Jasa Ekspedisi di PT. X Saudi Tanjung Bumi Bangkalan - Alim, M Zainal; Kurriwati, Nirma Kurriwati (Jurnal Kajian Ilmu Manajemen (JKIM), 2025)
This research aims to explore the influence of service quality and price perception on customers’ intention to reuse expedition services offered by PT. X Saudi Tanjung Bumi Bangkalan. The study employed a quantitative method with purposive sampling, targeting 77 respondents who had utilized the company’s services within the past six months. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the SmartPLS 4 application. The findings reveal that both service quality and price perception significantly and positively affect repurchase intention, whether considered individually or simultaneously. These results imply that maintaining high service standards alongside fair and competitive pricing strategies can strengthen customer loyalty and encourage repeat usage of the company’s services.